Pengaruh Olahraga Step Up terhadap Massa Tulang pada Wanita Dewasa Muda - Rungkat, Timotius A.; Lintong, Fransiska; Moningka, Maya E. W. (UNIVERSITAS SAM RATULANGI, 2020)
Abstract: Early detection and prevention are important indicators in maintaining bone mass. Age and sex are unmodifiable factors that contribute towards a reduction of bone mass. Preventive measures include consuming nutritions such as calcium and vitamin D, as well as physical activities like aerobic exercises inter alia step up exercise. This study was aimed to determine the effect of step up exercise on bone mass of young adult females. This was an experimental and analytical study with a one group pre and post test design. Respondents were 25 young adult females enrolleded in batch 2019 of the Nursing Program of Faculty of Medicine, Sam Ratulangi University. Step up exercise was conducted in a period of 6 weeks. Bone mass was measured using bioelectrical impedance analysis (BIA) before and after a 6-week step up exercise. The results showed the average bone mass of pre step up exercise was 1.85 kg and of the 6-week step up exercise was 1.92 kg. The Wilcoxon Signed Ranks Test statistical analysis of bone mass before and after the step up exercise obtained a p-value of 0,.00 (p<0.05 with a 95% Confidence Interval). In conclusion, there was a difference of bone mass before and after the 6-week step up exercise which meant that step up exercise could increase bone mass in young adult females.Keywords: step up exercise, bone massÂ Abstrak: Deteksi dini dan pencegahan merupakan indikator penting dalam mempertahankan massa tulang. Beberapa faktor yang tidak dapat dimodifikasi seperti usia dan jenis kelamin dapat menjadi sumber penurunan massa tulang. Upaya pencegahan yang dapat dilakukan ialah dengan mencukupi asupan nutrisi seperti kalsium dan vitamin D dan aktivitas fisik berupa olahraga aerobik, antara lain step up. Penelitian ini bertujuan untuk mengetahui pengaruh olahraga step up terhadap massa tulang pada wanita dewasa muda. Jenis penelitian ialah analitik eksperimental dengan one group pre and post test design. Responden penelitian ialah 25 mahasiswa program studi Ilmu Keperawatan Fakultas Kedokteran Universitas Sam Ratu-langi angkatan 2019. Olahraga step up dilakukan selama 6 minggu. Massa tulang diukur menggunakan bioelectrical impedance analysis (BIA) sebelum dan sesudah 6 minggu olahraga step up.. Hasil penelitian mendapatkan rerata massa tulang sebelum olahraga step up 1,85 kg dan rerata massa tulang sesudah olahraga step up selama 6 minggu 1,92 kg. Uji statistik Wilcoxon Signed Ranks Test terhadap massa tulang sebelum dan sesudah olahraga step up memperoleh nilai p=0,000 (p<0,05 untuk Confidence Interval 95%). Simpulan pene-litian ini ialah terdapat perbedaan massa tulang sebelum dan sesudah olahraga step up selama 6 minggu, yang berarti olahraga step up dapat meningkatkan massa tulang pada wanita dewasa muda.Kata kunci: olahraga step up, massa tulang